Determinants of technical efficiency in the Zimbabwean manufacturing industries - Munongo, Simon; Chitungo, Shallone. K (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
This study investigates the determinants efficiency of manufacturing subsectors in the Zimbabwean economy. The study applied the panel data econometrics approach in the leading manufacturing subsectors from 1980-2005. The technical efficiency estimates using SFA shows that there are varying efficiencies across sub-sectors and through time. The log-likelihood test shows that there existed technical inefficiency in the production processes in the manufacturing sector. This shows that the industries could improve their productive capacities with the same amount of inputs. The study shows that in the Zimbabwean manufacturing industries between 1980 and 2005 industries with strong the human capital development and foreign direct investment flowsÂ  had higher efficiency. The concentration of foreign owned firms in an industry and capital intensity had no effect on the efficiency of an industry.